2013
DOI: 10.1590/s1983-40632013000200002
|View full text |Cite
|
Sign up to set email alerts
|

Lodo de esgoto e vermiculita na produção de mudas de eucalipto

Abstract: O êxito de plantios florestais não está ligado, unicamente, à espécie utilizada, mas depende, diretamente, do tipo de recipiente, da qualidade das sementes e do substrato utilizado. Assim, objetivou-se avaliar a utilização de lodo de esgoto, juntamente com vermiculita, na composição de substratos, para a produção de mudas de Eucalyptus grandis provenientes de sementes. Adotou-se o delineamento inteiramente casualizado, com seis tratamentos e seis repetições de quatro plantas. Os tratamentos foram compostos pel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
13
0
19

Year Published

2013
2013
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 42 publications
(46 citation statements)
references
References 17 publications
4
13
0
19
Order By: Relevance
“…For vermiculite, the low performance as a substrate may be related to its high content of magnesium and iron which may have affected the calcium magnesium ratio of the medium and absorption of calcium and other nutrients by the plant. Caldeira et al (2013) suggest that vermiculite needs balancing of essential nutrients and should be used in conjunction with other material, preferably of organic origin, in order to promote aeration and porosity to other less porous substrates, in agreement with the results found in the experiment, where the addition of dry coconut powder to vermiculite promoted better results in the analyzed characteristics when compared to the use of vermiculite substrate without addition of other materials.…”
Section: Resultssupporting
confidence: 87%
“…For vermiculite, the low performance as a substrate may be related to its high content of magnesium and iron which may have affected the calcium magnesium ratio of the medium and absorption of calcium and other nutrients by the plant. Caldeira et al (2013) suggest that vermiculite needs balancing of essential nutrients and should be used in conjunction with other material, preferably of organic origin, in order to promote aeration and porosity to other less porous substrates, in agreement with the results found in the experiment, where the addition of dry coconut powder to vermiculite promoted better results in the analyzed characteristics when compared to the use of vermiculite substrate without addition of other materials.…”
Section: Resultssupporting
confidence: 87%
“…This links up the observations of Caldeira CALDEIRA JUNIOR et al, 2009 andCALDEIRA et al, 2013 found that on the field the best results in the survival of eucalyptus seedling are those substrates containing sewage sludge. These authors also noted that 2/1 of GPDM/RDM is a good balance for the growth of plants.…”
Section: Eucalyptus Camaladulensissupporting
confidence: 85%
“…According to Caldeira et al (2013), the SDM/RDM ratio is lower in environments of lower fertility and may be considered as a strategy of the plant, which invests in root growth instead of shoot growth to absorb as much as nutrients as possible under that condition. The same behavior was observed in this experiment, in which the lowest values of SDM/RDM were found in the treatment with commercial substrate.…”
Section: Resultsmentioning
confidence: 99%